Self-healing materials : principles & technology - Wypych, George (ChemTec Publishing, 2017)
"Self-healing phenomenon, adapted from living things, was for a long an interesting topic of potential improvement of human-made products, but for quite a while it became applicable reality useful in many manufactured product. The book has three major sections organized in fourteen chapters. The first section contains several chapters which discuss principle mechanisms of self-healing which can be potentially applied in the development of materials, which when damaged have an ability to repair themselves without or with minimal human intervention. All theoretical background required and known to-date to understand these principles is included in this section. The second section contains discussion of additives used in the formulating these products. And, the final section includes examples of the self-healing materials which belong to almost 40 groups of manufactured products. The attached table of contents contains more information about this book on the most modern technological developments. The expected audience for this book includes people working in industries listed in the chapter 14, university professors and students, those working on the reduction of wastes and recycling, and all environmental protection agencies."--